The effect of multi walled carbon nanotubes (MWCNTS) addition on the physical properties, hardness and toughness of ZTA-MgO cutting tool - Nor Ezzati Hamidon (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
The purpose of this study is to develop ZTA-MgO-MWCNT cutting insert with enhanced properties and excellent tool performance that is suitable for high speed machining. The effects of MWCNT addition on the physical properties, hardness and fracture toughness of ZTA-MgO composites were investigated. The samples was fabricated using 80:20 composition (80 wt.% of Al2O3: 20 wt.% of YSZ) with fixed amount of MgO at 1.1 wt.% and MWCNT ranging from (0.1 – 0.5 wt.%) as secondary additives. The CNT was pretreated in ethanol for 1 hour using an ultrasonic homogenizer before mixing and ball milled with Al2O3, YSZ and MgO compositions for 24 hours. The mixture is then pressed at 100 MPa into round-shaped cutting inserts mold after being dried at 100°C for 24 hour. The pressed samples were sintered at 1600 ºC for 4 hour soaking time. There are three parts in this study whereby the first part observed phase analysis by XRD and microstructure of the sintered samples using SEM. The XRD analyses indicate the presence of major phases were α-Al2O3, ZrO2, Zr0.963Y0.037O1.982 and MgAl2O4. Minor peak at (002) increases with higher MWCNT wt.% which suggest the presence of MWCNT in the composites. Samples with higher content of MWCNT beyond 0.3 wt.% possessed smaller grain size and refined microstructure compared to sample with low content of MWCNT. The second part analysed the effect of MWNT addition on density, porosity and shrinkage of ZTA-MgO. Density (4.210 g/cm3) and percentage of shrinkage (8.05%) obtained the highest value by 0.2 wt.% MWCNT compared with samples without CNT additives which is only 4.020 g/cm3 and 7.05% respectively. High density value would mean the shrinkage percentage is also high, which corresponds to the densification of the composites. Poor dispersion of MWCNT within the matrix is highly accounted for agglomeration around Al2O3 grain boundaries and decreases in densification. The third part focused on hardness and fracture toughness after adding MWCNT on the ZTA-MgO composites. Results shows that ZTA-MgO samples with 0.2 wt.% MWCNT produced the highest hardness (19.93 GPa). The increment of hardness was contributed by the inhibition grain growth in Al2O3 due to pinning effect of MWCNT at grain boundaries. It is observed that fracture toughness increases from 3.8 MPa•√m to 8.08 MPa•√m with addition of 0.2 wt.% MWCNT. The improvement of fracture toughness is possibly due to the transformation toughening mechanism of t‐ZrO2 to m‐ZrO2. Results of hardness and fracture toughness exhibit that ZTA-MgO with additions of 0.2 wt.% MWCNT is the best composition for ceramic cutting tools application.